Listen Up, Everyone! Conquering Students' Inattentiveness When You're the Guest Lecturer. - Giovanna Badia (Issues in Science and Technology Librarianship)
The article discusses strategies for instructors on capturing students' attention in a guest lecture or one-shot class. Strategies described include understanding students' needs, obtaining buy-in, showing enthusiasm and incorporating in-class activities. Other topics cited include ways to demonstrate one's passion for the subject being taught and recommended in-class activities.